Gut Microbiome as a Potential Marker of Hematologic Recovery Following Induction Therapy in Acute Myeloid Leukemia Patients - Valentina Salvestrini; Gabriele Conti; Federica D'Amico; Gianluca Cristiano; Marco Candela; Michele Cavo; Silvia Turroni; Antonio Curti (Cancer Medicine, 2025)
ABSTRACT Background The management of acute myeloid leukemia (AML) is hindered by treatment‐related toxicities and complications, particularly cytopenia, which remains a leading cause of mortality. Given the pivotal role of the gut microbiota (GM) in hemopoiesis and immune regulation, we investigated its impact on hematologic recovery during AML induction therapy. Methods We profiled the GM of 27 newly diagnosed adult AML patients using 16S rRNA amplicon sequencing and correlated it with key clinical parameters before and after induction therapy. Results Our investigation revealed intriguing associations between the GM composition and crucial recovery indicators, including platelet, lymphocyte, and neutrophil counts, and identified early GM signatures predictive of improved hematologic recovery. Remarkably, patients demonstrating superior recovery had higher alpha diversity and enrichment in health‐associated taxa belonging to the genera Faecalibacterium, Ruminococcus, Blautia, and Butyricimonas at diagnosis. Conclusions Despite certain study limitations, our findings suggest that evaluating GM features could serve as a potential marker for hematologic recovery. This preliminary work opens avenues for personalized risk assessment and interventions, possibly involving GM modulation tools, to optimize recovery in AML patients undergoing induction therapy and potentially enhancing overall outcomes in individuals with hematologic diseases.